Application and suitability analysis of the key technologies in nearly zero energy buildings in China. (March 2019) - Liu, Zhijian; Liu, Yuanwei; He, Bao-Jie; Xu, Wei; Jin, Guangya; Zhang, Xutao
Abstract: The energy consumption in buildings accounts for a significant proportion of total energy and carbon emissions over the world. To reduce the building energy consumption and achieve sustainable development of buildings, nearly zero energy buildings (NZEBs) have attracted widespread attention as a future building energy target. This paper reviews energy-efficient measures (EEMs) and renewable energy technologies (RETs) in NZEBs and discusses the application and suitability of the key technologies, i.e. minimizing the energy demand in NZEBs by EEMs and adopting RETs to meet the remaining energy needs. EEMs contain efficient thermal insulation system, high-performance window system, good airtightness and fresh air heat recovery system. RETs are composed of solar photovoltaic/thermal (PV/T) system, air source heat pump system (ASHP), ground source heat pump system (GSHP), and wind power. In addition, this paper emphasizes further research works, which involve life cycle energy analysis (LCEA), meteorological parameters change, intelligent building operation management (IBOM) system, energy storage system and social policy issues. This paper will provide some references for the further development of NZEBs in different climatic regions in China. Highlights: This paper systematically reviews application of EEMs and RETs in NZEBs in China. Feasibility and suitability of EEMs and RETs are evaluated from different aspects. Further research work and development direction of NZEBs are pointed out.